Effectiveness of Online Advertisement Towards Hotel Booking In Seda Hotel Vertis North: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Seda Hotel is undergoing an Online Hotel Booking System project to offer consumersthroughout the world a quick and simple option to book hotels online. Web pages that may beaccessed through a website browser make up the interface of the online hotel bookingsystem. Users can access the system anytime, anywhere, and use it to book rooms at SedaHotel. The Online Hotel Booking System is a user-friendly program. Following its easy andstraightforward GUI (Graphical user interface) design, anyone who knows how to use a Webbrowser may quickly make a booking, update the booking details, cancel the booking, changethe personal profile, examine the booking history, or view the hotel information.The results of this study reveal that the hotel is doing a great job in providing guest satisfactionto the customers. The respondents asked how effective online advertisements are in hotelaccommodations and the challenges or issues encountered in online advertisements towardsthe hotel, booking as agreed.It was determined that customer contentment with the Environment, Service, and Amenitieswas highly noticed. Except for Reach and Presentation, where the survey indicated thatcustomers had the lowest satisfaction level, the hotel is advised to maintain the quality of theoperations that rated with the highest satisfaction and observation.
Keywords: Business